KORESPONDENSI FONEMIS BAHASA OGAN DAN BAHASA BANGKA: KAJIAN LINGUISTIK HISTORIS KOMPARATIF - Nikolaus Rendi Prasetya Hadi; Sintaria Kusumaningrum (Jurnal CULTURE (Culture, Language, and Literature Review), 2020)
The objects of this research are Organese and Bangkanese language. The objectives of this research are to describe phonemic correspondence of Organese and Bangkanese language, and to compare the phonemic correspondence formula of both languages. The data of this research are phonemes from both languages which was gathered using dictionary study method with taking-note technique. The phoneme data searched were phonemes in which they have correspondence value. There are several findings in this research, they are: (1) proto-phoneme */u/ retained in Bangkanese, while in Organese is reflected as phoneme /o/. The reflection occurs in closed-ultima positions, if followed by bilabial plosive-stop /m/, nasal dorso-velar /ŋ/, glottal slide /h/. dorso-velar plosive-stop /k/, and apicodental plosive stop /t/; (2) proto-phoneme */a/ retained in Organese, while in Bangkanese is reflected as /Ə/. The reflection occurs in closed-ultima positions, if followed by bilabial plosive-stop /p/, glottal slide /h/, apico-lateral /r/, nasal dorso-velar /ŋ/, bilabial plosive-stop /m/, apicodental plosive-stop /t/, lateral /l/, nasal apico-alveolar /n/, and glottal plosive-stop /Ɂ/; and (3) proto-phoneme */h/ retained in Bangkanese, while in Organese is either reflected as /ø/ or being eliminated. The particular reflection occurs in penultima positions, if followed by vowels /a/, /i/, and /u/.